PENETAPAN RETENTION TIME PROGESTERON DALAM PELARUT ELUEN PHASE MOBILE MENGGUNAKAN HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Chandra, Evania Haris; Lazuardi, Mochamad; Sarudji, Suryanie; Maslachah, Lilik; Sukmanadi, Mohammad; Utama, Suzanita (Journal of Basic Medical Veterinary, 2020)
The aim of this research was to determine the level of stability of Progesterone-retention time on Eluen Phase Mobile (EPM) solution in storage period for six, eight and 12 hours using High Performance Liquid Chromatography (HPLC). The research method used posttest-only control group design by using three treatments and six repetitions. The three repetitions consist into six hours, eight hours and 12 hours. The data were obtained analyzed by Summery Independent T-Test with SPSS 24 for windows. The results showed that the progesterone treatment in EPM solvents with six-hour storage (P1) and eight hours (P2) retention time progesterone are stable but the progesterone treatment in EPM solvent with 12-hour storage (P3) showed an unstable due to storage time. Besides that there are irrelevant peak which show that many pure molecular fractions are separated in the stationary phase so that the molecular structure of the substance begins to break down. Based on these results, it can be concluded that the storage time of Progesterone in Eluen Phase Mobile began to be unstable at 12 hours of storage.